Molecular regulatory mechanisms and diagnostic potential of dendritic cell-derived exosomes in liver transplantation: from immune tolerance induction to translational challenges - Chen, Xiaopeng; Yang, Zhiqi; Li, Minghao (Frontiers in Immunology, 2025)
Liver transplantation remains the only curative treatment for end-stage liver disease (ESLD); however, immune rejection significantly hampers its long-term success. Dendritic cell-derived exosomes (DEXs) have emerged as a promising tool for inducing immune tolerance and enabling precise immunomodulation in liver transplantation, owing to their unique bidirectional immunoregulatory capabilities. This review systematically summarizes the biological characteristics and functional properties of DEXs, with a particular focus on their multidimensional regulatory mechanisms within the hepatic transplant immune microenvironment. These include: the mechanisms and pathways by which DEXs mediate immune tolerance; the synergistic immunoregulatory roles of DEXs and exosomes derived from other immune cells. Furthermore, we explore the potential of DEXs for integrated diagnostic and therapeutic applications, engineering upgrades to treatment strategies, and their prospects for clinical translation. Despite their promise, several challenges persist, including difficulties in exosome isolation and purification, prolonged preparation times, bioengineering limitations, and the lack of effective in vivo tracking methods. We propose that advancements in artificial intelligence, biomaterials science, and interdisciplinary technologies may help overcome these barriers, facilitating the precise isolation, functional optimization, and clinical translation of DEXs. This review emphasizes the molecular immunoregulatory networks governed by DEXs and discusses their translational pathways, aiming to promote individualized diagnostic and therapeutic strategies in liver transplantation.